Lexical anglicisms: An analysis of commercials addressed to young children on four Television Channels in Spain - Luján-García, Carmen (Onomázein, 2015)
The influence of English in Spanish has led to the use of a considerable number of pure anglicisms to designate child-related concepts. This paper intends to examine the degree of exposure of children to English terms by analysing the increasing presence of anglicisms in Spanish television commercials. With that purpose, the amount and the kinds of anglicisms present on TV commercials of four popular TV channels in Spain (Antena 3, Tele 5, La Sexta and Disney Channel) have been explored. The study reveals that English borrowings are quite present in different subject areas (food and drinks; games and toys; clothes and shoes; personal hygiene; leisure and entertainment). A classification of pure anglicisms, adapted anglicisms, pseudo-anglicisms, and acronyms has been made, and some Anglo-American cultural icons have been analysed. English usage in global advertising is a marker of modernity, progress, sophistication. Findings in this research reveal that children in Spain are considerably exposed to this influence.